2011
DOI: 10.1089/ars.2010.3468
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na+/H+ Exchanger Isoform 1 Is Neuroprotective in Neonatal Hypoxic Ischemic Brain Injury

Abstract: We investigated the role of Na(+)/H(+) exchanger isoform 1 (NHE-1) in neonatal hypoxia/ischemia (HI). HI was induced by unilateral ligation of the left common carotid artery in postnatal day 9 (P9) mice, and subsequent exposure of animals to 8% O(2) for 55 min. A pre/posttreatment group received a selective and potent NHE-1 inhibitor HOE 642 (0.5 mg/kg, intraperitoneally) 5 min before HI, then at 24 and 48 h after HI. A posttreatment group received HOE 642 (0.5 mg/kg) at 10 min, 24 h, and 48 h after HI. Saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…The body temperature of the animals was maintained at 37°C with a heating pad. Under a surgical microscope, a midline skin incision was made, and the left common carotid artery electrically cauterized as described before [12]. The incision was rinsed with 1% lidocaine and sutured with a 6-0 Prolene suture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The body temperature of the animals was maintained at 37°C with a heating pad. Under a surgical microscope, a midline skin incision was made, and the left common carotid artery electrically cauterized as described before [12]. The incision was rinsed with 1% lidocaine and sutured with a 6-0 Prolene suture.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported that pharmacological inhibition of Na + /H + exchanger isoform 1 (NHE1) activity in postnatal day (P)9 mice protected hippocampal neurons at 3 days after HI [12]. Neonatal mice that were treated with HOE 642 (a potent and selective inhibitor of NHE1) showed improved motor and spatial learning at P60.…”
Section: Introductionmentioning
confidence: 99%
“…The Na + /H + Exchanger-1 as a New Molecular Target in Stroke Interventions and hippocampus and improved performance on tests of motor learning and memory (Cengiz et al, 2010). These findings suggest that NHE-1 mediated disruption of ionic homeostasis can contribute to CA1 pyramidal neuronal injury after neonatal HI.…”
Section: Hypoxia/ischemiamentioning
confidence: 82%
“…NHE-1 activity in astrocytes (Cengiz et al, 2010), neurons (Manhas et al, 2010), and microglia ) is stimulated following cerebral ischemia. Excessive stimulation of NHE-1 leads to intracellular Na + overload, and in turn causes a rise in intracellular Ca 2+ due to increased Ca 2+ influx via reversal of the Na/Ca exchanger.…”
Section: Role Of Nhe-1 In Cellular Dysfunction and Cerebral Injury Dumentioning
confidence: 99%
See 1 more Smart Citation